1991
DOI: 10.1002/ijc.2910470418
|View full text |Cite
|
Sign up to set email alerts
|

The role of the peyer's patch in the carcinogenesis of lymphoid cells

Abstract: The dose response to 3-methylcholanthrene (3-MC), the promoter effects of 2,6,10,14-tetramethylpentadecane (pristane) and the target-organ specificity in the preferential induction of B-lymphoid malignancies versus thymic tumors were examined. Lymphoid malignancies were induced in approximately 30% of the Copenhagen rats treated with injections in Peyer's patches (PP) of low, intermediate or high doses of 3-MC. A low dose of 3-MC induced B-lymphocytic leukemias or B lymphomas, whereas thymic tumors were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies to address the possible basis for the pristane-induced changes in the DNA staining characteristics of lymphocytes demonstrated that 1 ) there were no decreases in the amount of DNA present in the nuclei, 2) nuclei isolated from pristane treated rats were less sensitive to thermal denaturation, as well as DNase I enzymatic digestion, and 3) there were apparent increases in the expression of the HI histone proteins. Collectively, these results suggest that pristane elicits a conformational change in the chromatin which may be mediated by altered expression of nuclear-associated histone proteins.Key words: 2,6,10,14-tetramethylpentadecane, histone, DNA conformation, pristane, lymphocyte Pristane also elicits a promoter-like response in that treatment with 3-methylcholanthrene (3-MC) resulted in few lymphoid malignancies, whereas treatment with 3-MC and pristane resulted in the induction of lymphoid leukemias and lymphomas in > 60% of the rats examined [11][12][13]. Furthermore, while the above mentioned biological effects of pristane suggest that Lenora R. Garrett's current address is Tumor Biology, Fred…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies to address the possible basis for the pristane-induced changes in the DNA staining characteristics of lymphocytes demonstrated that 1 ) there were no decreases in the amount of DNA present in the nuclei, 2) nuclei isolated from pristane treated rats were less sensitive to thermal denaturation, as well as DNase I enzymatic digestion, and 3) there were apparent increases in the expression of the HI histone proteins. Collectively, these results suggest that pristane elicits a conformational change in the chromatin which may be mediated by altered expression of nuclear-associated histone proteins.Key words: 2,6,10,14-tetramethylpentadecane, histone, DNA conformation, pristane, lymphocyte Pristane also elicits a promoter-like response in that treatment with 3-methylcholanthrene (3-MC) resulted in few lymphoid malignancies, whereas treatment with 3-MC and pristane resulted in the induction of lymphoid leukemias and lymphomas in > 60% of the rats examined [11][12][13]. Furthermore, while the above mentioned biological effects of pristane suggest that Lenora R. Garrett's current address is Tumor Biology, Fred…”
mentioning
confidence: 98%
“…Pristane also elicits a promoter-like response in that treatment with 3-methylcholanthrene (3-MC) resulted in few lymphoid malignancies, whereas treatment with 3-MC and pristane resulted in the induction of lymphoid leukemias and lymphomas in > 60% of the rats examined [11][12][13]. Furthermore, while the above mentioned biological effects of pristane suggest that pristane may act indirectly to elicit the corresponding effects, previous studies in our laboratory indicate that pristane may have a more direct effect on the cellular DNA.…”
mentioning
confidence: 99%